Hydraulic and hygrothermal properties of lightweight concrete blocks with basaltic lapilli as aggregate. (30th September 2015) - Sánchez Fajardo, V.M.; Torres, M.E.; Moreno, A.J.
Highlights: Determination of the pore structure parameters by MIP and dielectric spectroscopy. Measurement of the thermal conductivity in different relative humidity conditions. Strong correlation between liquid permeability and pore connectivity parameters. Comparison between dry and wet thermal conductivity shows great differences for all samples. Abstract: The concrete block with lapilli (LCB) is commonly used in the Canary Islands. The basaltic lapilli is an aggregate of volcanic origin which provides a low density and thermal conductivity to LCBs due to its high porosity. But water retention is the main disadvantage of this block, because thermal insulation properties are severely compromised. In this study an analysis of the hygrothermal behavior of LCB by dielectric spectroscopy (DS), mercury intrusion porosimetry (MIP) and thermal conductivity determination has been performed. The results of this work provided strong correlations between pore parameters (mainly critical pore diameter and pore connectivity) and liquid permeability.